Acceleration of Iron Utilization After Intravenous Iron Administration During Activated Erythropoiesis in Hemodialysis Patients: A Randomized Study. Issue 2 (26th September 2014) - Kuji, Tadashi; Toya, Yoshiyuki; Fujikawa, Tetsuya; Kakimoto‐Shino, Midori; Nishihara, Masahiro; Shibata, Kazuhiko; Tamura, Kouichi; Hirawa, Nobuhito; Satta, Hidehisa; Kawata, Sei‐ichi; Kouguchi, Naoaki; Umemura, Satoshi
Abstract This study aimed to evaluate the effect of different timings of iron administration during erythropoiesis activated by continuous erythropoietin receptor activator (CERA) on reticulocyte iron uptake in hemodialysis patients. In total, 110 patients were randomized to receive 40 mg intravenous elemental iron doses at all three hemodialysis sessions in the first week (IW1 group: n = 57) or in the third week (IW3 group: n = 53) after CERA administration. Following CERA administration at day 0, reticulocyte count increased, peaking at day 7. At days 7 and 14, the observed changes in Ret‐He were higher in the IW1 group than in the IW3 group. Increases in total reticulocyte hemoglobin at day 7 were higher in the IW1 group than in the IW3 group. In contrast, there was only tendency toward greater total reticulocyte hemoglobin after iron administration in the third week in the IW3 group. Intravenous iron supplementation in the first week of CERA administration increases reticulocyte iron uptake; however, iron supplementation in the third week does not. The findings indicate that iron should be intravenously administered to increase the efficacy of CERA within 1 week of CERA administration during highly active erythropoiesis.